Reflection of Cardinal Stefan Wyszyński on the topic social education in Poland. Selected theorems and their relevance - Chrostowski, Mariusz (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
Despite the fact that the pedagogical legacy of Cardinal Stefan Wyszyński has a historical character and was created in a completely different way in today's socio-political context, it does not lose its topicality. This is mainly due to the fact that it was created by This outstanding Pole's vision of the concept of social education is built around the assumptions of an integral vision of the human person, and is also reflected in the timeless educational prerogatives. In this context, the aim of this article is a theoretical analysis of Cardinal Stefan Wyszyński's reflections on social education in Poland. The author begins by presenting a sketch of the biography of „Prymasa Tysiąclecia”, which is a kind of overture to discuss the most important ones Cardinal Stefan Wyszyńskis Denken über die Sozialerziehung in Polen. Einige ausgewählte Behauptungen und deren Aktualität heute aspects of his vision of social education, i.e. the family context, national and religious state. The whole considerations are crowned with an attempt to show the topicality of the primate's socio-pedagogical thought.